Legal Innovations to Advance a Culture of Health. Issue 4 (2015) - Hodge, James G.; Weidenaar, Kim; Baker-White, Andy; Barraza, Leila; Bauerly, Brittney Crock; Corbett, Alicia; Davis, Corey; Frey, Leslie T.; Griest, Megan M.; Healy, Colleen; Krueger, Jill; Lowrey, Kerri McGowan; et al.
Abstract : Since its inception in 2010, the Network for Public Health Law (Network) has aligned with federal, state, tribal, and local public health practitioners to assess how law can promote and protect the public's health. In 2013, Network authors illustrated major trends in public health laws and policies emanating from an internal assessment of thousands of requests for technical assistance nationally. More recently, the Robert Wood Johnson Foundation (RWJF) has invited the Network and other partners to consider new ideas and strategies toward building a "culture of health." Per Figure 1, RWJF's conception of a culture of health emphasizes key action areas essential to the promotion of health across all sectors and diverse populations.